(untitled) (Journal of Nepal Geological Society, 2020)
Lakes are the environmental and socioeconomic assets of Nepal. In the past few decades, land use and land cover (LULC) change has severely altered the lake ecosystems. The sediment and nutrients loading into the lakes have altered lake ecosystem significantly. This study analyzes the spatiotemporal variations of LULC change and examines its impact on lake environment of Phewa, Begnas and Rupa lakes during 1975–2018 by using Landsat satellite images and data from published literatures. Results showed that from 1975 to 2018, forest cover and agriculture land in catchments of all three lakes has decreased, while the built-up area has increased. LULC change in the catchment have bought the significant impact on the lake environment in terms of sedimentation rate, physiochemical parameters and biological environment. From 1975 to 2000 forest cover in lakes catchment has decreased, whereas the agriculture land has increased. At the same time, sediment and agriculture based nutrient loading into lakes has increased indicated by changes in sedimentation rate and alteration of physiochemical properties of the lake. From 2000 to 2018, forest and built-up area has increased while the agriculture land has decreased in lakes catchment. From 2000 to 2018, sedimentation rate of lakes has decreased compared to before 2000. Decreased sedimentation rate was interpreted due to increase in forest cover in the lake catchment. Increased nutrients loading into the lake during 2000 to 2018 has resulted serious eutrophication problem in lakes. Overall, this study suggests that the LULC change in the catchment have significant impact on lake environment.